Antidiabetic action of combined medicine glikverin in terms of experimental Diabetes Mellitus type 2 - O. M. Chikitkina; N. M. Kononenko; V. V. Chikitkina; Y. B. Lar'yanovskaya (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2015)
Antidiabetic action of a new composition Glikverin was investigated in experimental DM in rats caused by streptozotocin on the background of nicotineamide. It was established that combination of quercetin and voglibose in one remedy determines more significant antidiabetic action than of these components separately. The influence on glicaemia level and lipid peroxidation/anbtioxidative system indexes on this model was of the same significance in Glikverin and standard reference agent tablets metformin. The efficacy of a new composition is confirmed by results of histological study. Positive influence on condition of pancreatic endocrine component in rats was more significant in Glikverin than in reference agents voglibose, quercetin and tablets metformin. Received data justifies and makes reasonable using Glikverin for correction of carbohydrate metabolism and inhibition of lipid peroxidation in terms of relative insulin resistance.